Adaptive advantage of Sesbania virgata (Cav.) Pers. in the phytochemical production: the influence on fungi occurring in seeds - Vera Lygia El Id Id; Nelson Augusto dos Santos Junior (Acta Scientiarum. Biological Sciences, 2023)
Sesbania virgata is a native Brazilian plant species. It exhibits rapid growth, a high soil cover potential, and efficient soil seed bank formation and is used in environmental restoration projects. The soil seed bank is susceptible to fungal infection and other biotic factors. However, only a few studies have reported on the fungi on the surface of S. virgata seeds. Moreover, little is known about how substances present in the seed integument affect fungal communities and their role in adapting to and thriving in new environments. Herein, S. virgata seeds were collected from populations that produce or do not produce the flavonoid catechin in the seed coat. These seeds were subjected to laboratory tests to identify and quantify the fungal populations in the integument. We selected and subjected three genera to irrigation and inoculation tests with S. virgata extracts and seeds from both populations. We observed that the aqueous seed coat extracts inhibited Alternaria sp. micellar and augmented Phoma sp. growth. Phoma sp. also caused post-germinated seed lethality. Our data indicate that the seed coat of S. virgata contains antifungal substances that endow this species with an adaptive advantage.